Financing emerging black farmers for agricultural development in South Africa: A wasteful and unworkable model for creating black farmers - Mokoko P. Sebola (The Journal for Transdisciplinary Research in Southern Africa, 2018)
The purpose of this article is to investigate the effectiveness of the model used by the South African government to finance emerging black farmers for agricultural development and empowerment. It is widely acknowledged that the South African government spends a vast amount of money attempting to help black community members become commercial farmers. In this article, I argue that those who currently qualify for the funding are mostly farmers with little experience, expertise or interest in agricultural farming. The huge investment spent on such farmers ends up being lost in failed agricultural projects, and the government has not succeeded in finding better alternatives to empower emerging black farmers. Such activities benefit neither the government nor the black farmers intended to be assisted in various areas of the country. The black South African farmers remain agriculturally underdeveloped, while the government on the other hand loses a huge amount of money financing unsuccessful agricultural projects, which potentially threatens future food security. This article is conceptual in nature and uses literature to argue that the financing of emerging black farmers can only succeed if emerging black farmers are financed on basis of experience or ability and interest in farming and that such funding does not exclude potential public and private sector motivated employees who want to access such funding to pursue agricultural farming.